The effect of antenatal education on expectant mother's childbirth attitudes, maternal role attainment, and self-confidence levels - POTUR, DİLEK (TAYLOR & FRANCIS INC, 2022)
We aim to determine the effect of antenatal education on the attitudes of expectant mothers toward birth, maternal role attainment and self-confidence levels. We carried out this quasi-experimental, non-randomized, prospective study in a hospital located in Istanbul, in the pre- and post-education model. Women in the education group (EG = 60) attended 6 weeks of education. Women in the control group (CG = 60) participated in a periodic follow-up visit. We collected the data using Childbirth Attitudes Questionnaire (CAQ), Pharis Self-Confidence Scale (PSCS), and Semantic Differential Scale-Myself as Mother (MMS). We made three measures in total: in the first visit, after six weeks and in the sixth week postpartum. We found the mean scores of second measurement of CAQ, PSCS, third measurement of MMS statistically significant in favor of EG (p < 0.05). Antenatal educations positively affect childbirth attitude, maternal role attainment and self-confidence levels. Supplemental data for this article is available online at https://doi.org/10.1080/07399332.2021.1935959 .
Keywords: RANDOMIZED-CONTROLLED-TRIAL; FEAR; EFFICACY; WOMEN; EXPERIENCES; IDENTITY